The role of vaccination and healthcare acquisition in respiratory failure during a COVID-19 outbreak in an acute hospital in Wales - Craig Hogg; Caoimhe McKerr; Noel Craine; Dafydd Williams; Malorie Perry; Simon Cottrell (Infection Prevention in Practice, 2025)
S U M M A R Y: This study provides descriptive analysis of a COVID-19 outbreak of 323 cases in a Welsh hospital in early 2021, with a focus on respiratory failure (RF) as a severe outcome. Multivariate analysis demonstrated decreased odds of RF in healthcare acquired cases (aOR 0.40 (95%CI 0.24–0.65), p<0.001) and individuals with at least one dose of vaccine 14 days before first positive test (aOR 0.45 (95%CI 0.28–0.75), p=0.002). In healthcare acquired cases, vaccination significantly reduced the odds of RF (OR 0.47 (95%CI 0.22-0.00), p=0.037). This analysis highlights the importance of vaccination as a protective factor against severe respiratory outcomes.